Health literacy on Mpox among Brazilian men who have sex with men: Findings from a national cross-sectional study - Santos, Guilherme Reis de Santana; Ribeiro, Caíque Jordan Nunes; Cepas, Lariane Angel; Bulcão, Carolina da Silva; Nascimento, Rita de Cassia Dias; Sousa, Anderson Reis de; Fronteira, Inês; Mendes, Isabel Amélia Costa; Fernandes, Ana Paula Morais; Sousa, Álvaro Francisco Lopes de (Belitung Nursing Journal, 2025)
Background: In 2022, Mpox presented significant challenges globally, particularly in Brazil, where cases surged among men who have sex with men (MSM). Health literacy (HL) is essential for promoting health within this group. Objective: To analyze the HL of MSM in the context of Mpox transmission in Brazil. Methods: This was a national cross-sectional study conducted in a virtual setting. An electronic survey was carried out from September to December 2022. A translated and adapted version of the Health Literacy Scale (HLS-14) and a questionnaire containing sociodemographic information, sexual behaviors, and knowledge and beliefs about Mpox were administered. The distribution of predictor variables across health literacy (HL) levels was explored descriptively. Associations between predictors and HL were analyzed using Pearson’s Chi-square test (p < 0.20 for inclusion in multivariate analysis). A generalized linear Poisson model with robust variance was used to estimate adjusted prevalence ratios (aPR) and 95% confidence intervals. Model fit was assessed with the omnibus test and information criteria (AIC, deviance, log-likelihood). Significance was set at p <0.05. Results: The final sample included 1,449 MSM, with an overall prevalence of 53.83% (n = 780) for satisfactory HL. In the bivariate analysis, 15 of the 27 variables met the statistical criterion (p <0.20) for inclusion in the multivariate model, with six retained in the final model. Reporting non-adherence to treatment if diagnosed with Mpox (aPR: 1.73; 95% CI: 1.44–2.07), a prior Mpox diagnosis (aPR: 1.17; 95% CI: 1.04–1.32), having a basic education level (aPR: 1.15; 95% CI: 1.02–1.31), using apps to seek sex (aPR: 1.15; 95% CI: 1.04–1.27), and seeking sex at parties and clubs (aPR: 1.14; 95% CI: 1.04–1.26) were independently associated with a higher prevalence of satisfactory HL. Conclusion: HL levels among MSM during the Mpox public health emergency in Brazil were low, shaped by individual, economic, and social factors. The findings can guide nursing practice regarding how MSM deal with information and make decisions in contexts of episodic health events, as well as the HL strategies to be implemented in nursing therapy.